Fluxes of dissolved organic carbon and nutrients via submarine groundwater discharge into subtropical Sansha Bay, China. (31st July 2018) - Wang, Guizhi; Han, Aiqin; Chen, Liwen; Tan, Ehui; Lin, Hui
Abstract: To evaluate the role that submarine groundwater discharge (SGD) plays in the carbon and nutrient budgets in subtropical Sansha Bay, southeastern China, radium isotopes were used as SGD tracers and investigated in the bay and surrounding groundwater. In general, the activity of radium isotopes ( 223, 224, 226, 228 Ra) decreased from the bay head to the outlet that connects with the East China Sea. Based on the ratio of 224 Ra and 228 Ra, the water age was estimated to be 5.49 ± 3.64 and 1.50 ± 0.83 days in winter and summer, respectively. A three end-member mixing model and a box model were set up based on the mass balance of 226 Ra and salinity to quantify SGD. The flux of SGD was calculated to be 9.33 ± 8.17 × 10 5 m 3 d −1 (3.8 ± 3.4 × 10 −3 m 3 m −2 d −1 ) in winter and 4.89 ± 3.35 × 10 6 m 3 d −1 (2.0 ± 1.4 × 10 −2 m 3 m −2 d −1 ) in summer, which were at least a few times less than the concomitant river discharge into the bay. In groundwater, an enrichment of dissolved inorganic nitrogen, phosphorus, and organic carbon was associated with relatively high activities of 226 Ra. The SGD-associated nutrient flux was 1.99 ± 1.74–95.0 ± 83.2 μmol m −2 d −1 in winter and 0–0.89 ± 0.55 mmol m −2 d −1 in summer of phosphate, 6.76 ± 5.92–7.21 ± 6.32 mmol m −2 d −1 in winter and 66.2 ± 40.8–93.6 ± 57.7 mmol m −2 d −1 in summer of dissolved inorganic nitrogen, and 1.20 ± 1.05–1.74 ± 1.52 mmol m −2 d −1 in winter and 5.93 ± 4.06–8.22 ± 5.63 mmol m −2 d −1 in summer of silicate. The flux of dissolved organic carbon via SGD was 0.17 ± 0.15–0.33 ± 0.29 mmol m −2 d −1 in winter and 1.31 ± 0.81–2.94 ± 1.81 mmol m −2 d −1 in summer. The flux of N carried by SGD into Sansha Bay was comparable to the estuarine flux in winter, while was an order of magnitude greater than the estuarine flux in summer. The minimum flux of silicate via SGD was about half as much as the estuarine flux in summer, while was an order of magnitude smaller than the estuarine flux in winter. The minimum SGD-associated P flux was at least two orders of magnitude smaller than the estuarine flux in both seasons. Therefore, SGD on embayment scale is an important pathway for nitrogen from land to sea. These great SGD-associated nutrient fluxes may contribute to eutrophication and hypoxia in such stratified embayment.